2017
DOI: 10.1021/acs.energyfuels.7b01542
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Thermal Bitumen Structure as the Pyrolysis Intermediate of Longkou Oil Shale

Abstract: The effects of pyrolysis temperature on the structure of thermal bitumen as the pyrolysis intermediate of Longkou oil shale are investigated through electron paramagnetic resonance spectroscopy, Fourier transform infrared (FTIR) spectroscopy, nuclear magnetic resonance (NMR) spectroscopy, gas chromatography–mass spectrometry (GC-MS), and X-ray photoelectron spectroscopy (XPS). Results indicate that the free radical concentration of thermal bitumen increases at a maximum temperature of 410 °C and then decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Gaseous products including C 1 -C 5 light hydrocarbons and inorganic gases were quantied using an external standard method. As reported previously, 23,24 the relative error of quantities for gaseous products measured using this device was less than 0.5%.…”
Section: Gaseous Product Determinationsupporting
confidence: 81%
“…Gaseous products including C 1 -C 5 light hydrocarbons and inorganic gases were quantied using an external standard method. As reported previously, 23,24 the relative error of quantities for gaseous products measured using this device was less than 0.5%.…”
Section: Gaseous Product Determinationsupporting
confidence: 81%
“…The second stage, between 200 and 540 • C, is the main oil shale pyrolysis stage; weight loss in this stage was 15.8%. The range 350-540 • C was the main weight loss range, accounting for 84.4% of the total stage weight loss; this is owing to the decomposition of organic matter such as kerogen and bitumen to release low-molecular-weight gaseous volatile matter [50]. Thus, the 350-540 • C range is considered to be the oil-producing stage of oil shale.…”
Section: Preparation Of Oil Shale Samplesmentioning
confidence: 99%
“…Therefore, the formation rate of thermal bitumen is higher than its decomposition rate at 390−450 °C while the case is vice versa at 450−540 °C. Wang et al [6] and Shi et al [21,22] also indicated that the thermal bitumen yield first increased and then decreased with increasing pyrolysis temperature. The investigators emphasized the transient nature of thermal bitumen during decomposition of oil shales.…”
Section: Thermogravimetric Analysismentioning
confidence: 96%
“…Figure 4 shows the FTIR spectra of asphaltene fractions that are composed of highly polar compounds with high molecular weights. Based on the reported FTIR absorption bands of thermal bitumen [21,22] and kerogen [27,28], a summary of the characteristic bands of some functional groups in asphaltenes is presented in Table 3. Figure 4 shows that as pyrolysis temperature increases from 420 to 450 °C, the intensity of the band at 1711 cm −1 decreases while the band at Fig.…”
Section: Ultimate Analysismentioning
confidence: 99%